FeS2 Nanoparticles Encapsulated in S/N Co-Doped Carbon Nanofibers With a Three-Dimensional Multi-Channel Structure for Lithium-Ion Batteries - Cao, Xiaochang; Zhang, Yi; Luo, Chujiang; Yin, Yansheng; Huang, Yingying (Frontiers in Chemistry, 2022)
Graphical Abstract Graphical Abstract Novel FeS2@CNFs nanocomposites with the multi-channel structure were successfully prepared using the electrospinning method. The three-dimensional interlinked multi-channel carbon nanofibers can facilitate the diffusion of Li+ ions and electrons. Meanwhile, the FeS2 nanoparticles are distributed on the inner wall of the carbon nanofibers, improving the phenomenon of volume expansion for FeS2 and preventing the dissolution of polysulfide during the cycling process. In addition, co-doped S/N can supply abundant active sites for electrochemical reactions, providing enough space for Li+ ion storage. The FeS2@CNFs and the preparation method have exceptional applications in the field of energy storage.